Energy-conversion efficiency and power output of twisted-filament artificial muscles. (January 2022) - Wang, Shijun; Xiao, Ye; Xu, Zhiping
Abstract: Artificial muscles are materials or devices producing work under external stimuli. Recently-developed twisted-filament artificial muscles share a two-step process of triggered rotation or contraction, that are, volumetric expansion and tension-torsion coupling. Various actuating mechanisms such as thermal expansion, electrochemical cues, solvents absorption were proposed. We model the actuation processes of artificial muscles made of carbon nanotubes by numerical simulations and a simplified theoretical model. The underlying mechanical principles are elucidated, and the performance in terms of work output is quantified. The power output and energy-conversion efficiency of the muscles are then evaluated, showing the opportunity to further elevate their performance. The strategy to improve the muscle performance is also outlined through their dependence on the geometrical and material parameters. Highlights: Actuation in artificial muscles made of twisted microfilaments is resolved. Work output is calculated as a function of the geometrical and material parameters. Upper limits of the energy-conversion efficiency and power output are estimated.